PENGARUH PEMASARAN SYARIAH TERHADAP KEPERCAYAAN KONSUMEN DI BANK SYARIAH - dianhidayatii03; Muhammad Iqbal Fasa (Cipta Kind Publisher, 2024)
This study aims to analyze the influence of Islamic marketing on consumer trust in Islamic banks. Using a quantitative approach, data were collected through questionnaires distributed to customers of Islamic banks. The analysis results show that transparent, ethical, and value-based Islamic marketing significantly enhances customer trust. This study also identifies the challenges faced by Islamic banks, such as the lack of public understanding of Islamic products and the negative stigma associated with them. Based on these findings, it is recommended that Islamic banks enhance educational programs, transparency, and collaboration with third parties to strengthen consumer trust.